Evidence of added value in North American regional climate model hindcast simulations using ever-increasing horizontal resolutions - Lucas-Picher, Philippe; Laprise, René; Winger, Katja (Climate Dynamics, 2017)

North America Extratropical Cyclone (NAEC) Catalogue - Chen, Ting-Chen; Di Luca, Alejandro; Winger, Katja (Borealis, 2022)
The NAEC catalogue comprises information on extratropical cyclone (ETC) tracks in North America (20–80 N and 180-0W) from January 1979 to December 2020. The source data used to produce this dataset is obtained from the ECMWF ERA5 reanalysis at 1-hour spatial resolution and 0.25x0.25 degree spatial resolution. In addition to the location, time, and intensity, this dataset also includes ETC-associated impact variables such as the near-surface wind speed, wind gust, and precipitation, averaged using different radii around the ETC center. Both absolute and relative (to the local climatology) measures are provided. This catalogue provides useful information for the assessment of ETC-induced impacts over North America.

Seasonality of Continental Extratropical‐Cyclone Wind Speeds Over Northeastern North America - Chen, Ting‐Chen; Di Luca, Alejandro; Winger, Katja; Laprise, René; Thériault, Julie M. (Geophysical Research Letters, 2022)
Abstract This study investigates the seasonality of near‐surface wind speeds associated with extratropical cyclones (ETCs) over northeastern North America using a global reanalysis data set during 1979–2020. As opposed to most studies that emphasize winter storms, ETCs during the fall exhibit significantly stronger 10‐m winds over this region due to the slightly stronger continental cyclones and significantly weaker low‐level stability during that time of the year. Also, ETCs favor inland lakes and Hudson Bay during the low‐ice‐content fall season, leading to lower surface roughness. Combining these results, we derive simple linear regressions to predict the 10‐m wind speed given three variables: 850‐hPa wind speed, low‐level Richardson number, and surface roughness length. This formula captures the observed seasonality and serves as a valuable tool for cyclone near‐surface wind risk assessment. , Plain Language Summary Extratropical cyclones can bring powerful winds that can cause severe damage to infrastructure. We find that cyclones with severe winds are the most frequent in the fall season over continental northeastern North America. Three reasons are found responsible: stronger continental cyclones, weaker low‐level atmospheric stability, and the lower surface roughness over lakes and Hudson Bay, where cyclones frequently occur in fall. A simple formula that can effectively assess the near‐surface wind speeds associated with cyclones is derived based on these results. , Key Points Extratropical‐cyclone‐associated 10‐m wind speeds are the strongest in the fall season over northeastern North America Besides stronger continental cyclones and 850‐hPa winds, weaker low‐level stability in fall favors stronger 10‐m wind speeds in this region Linear regression using 850‐hPa wind, Richardson number, and surface roughness well predicts cyclones' 10‐m wind speeds and seasonality

Dynamical downscaling with the fifth-generation Canadian regional climate model (CRCM5) over the CORDEX Arctic domain: effect of large-scale spectral nudging and of empirical correction of sea-surface temperature - Takhsha, Maryam; Nikiéma, Oumarou; Lucas-Picher, Philippe; Laprise, René; Hernández-Díaz, Leticia; Winger, Katja (Climate Dynamics, 2018)

Changes in climate extremes in Zambia during green and dry Sahara periods and their potential impacts on hominid dispersal - Pausata, Francesco S.R.; Alain, Dominic; Ingrosso, Roberto; Winger, Katja; Drapeau, Michelle S.M.; Burke, Ariane (Quaternary Science Reviews, 2023)

Atlantic hurricane response to Saharan greening and reduced dust emissions during the mid-Holocene - Dandoy, Samuel; Pausata, Francesco S. R.; Camargo, Suzana J.; Laprise, René; Winger, Katja; Emanuel, Kerry (Climate of the Past, 2021)
Abstract. We use a high-resolution regional climate model to investigate the changes in Atlantic tropical cyclone (TC) activity during the period of the mid-Holocene (MH: 6000 years BP) with a larger amplitude of the seasonal cycle relative to today. This period was characterized by increased boreal summer insolation over the Northern Hemisphere, a vegetated Sahara and reduced airborne dust concentrations. A set of sensitivity experiments was conducted in which solar insolation, vegetation and dust concentrations were changed in turn to disentangle their impacts on TC activity in the Atlantic Ocean. Results show that the greening of the Sahara and reduced dust loadings (MHGS+RD) lead to a larger increase in the number of Atlantic TCs (27 %) relative to the pre-industrial (PI) climate than the orbital forcing alone (MHPMIP; 9 %). The TC seasonality is also highly modified in the MH climate, showing a decrease in TC activity during the beginning of the hurricane season (June to August), with a shift of its maximum towards October and November in the MHGS+RD experiment relative to PI. MH experiments simulate stronger hurricanes compared to PI, similar to future projections. Moreover, they suggest longer-lasting cyclones relative to PI. Our results also show that changes in the African easterly waves are not relevant in altering the frequency and intensity of TCs, but they may shift the location of their genesis. This work highlights the importance of considering vegetation and dust changes over the Sahara region when investigating TC activity under a different climate state.

On the Intercontinental Transferability of Regional Climate Model Response to Severe Forestation - Asselin, Olivier; Leduc, Martin; Paquin, Dominique; Di Luca, Alejandro; Winger, Katja; Bukovsky, Melissa; Music, Biljana; Giguère, Michel (Climate, 2022)
The biogeophysical effects of severe forestation are quantified using a new ensemble of regional climate simulations over North America and Europe. Following the protocol outlined for the Land-Use and Climate Across Scales (LUCAS) intercomparison project, two sets of simulations are compared, FOREST and GRASS, which respectively represent worlds where all vegetation is replaced by trees and grasses. Three regional climate models were run over North America. One of them, the Canadian Regional Climate Model (CRCM5), was also run over Europe in an attempt to bridge results with the original LUCAS ensemble, which was confined to Europe. Overall, the CRCM5 response to forestation reveals strong inter-continental similarities, including a pronounced wintertime and springtime warming concentrated over snow-masking evergreen forests. Crucially, these northern evergreen needleleaf forests populate lower, hence sunnier, latitudes in North America than in Europe. Snow masking reduces albedo similarly over both continents, but stronger insolation amplifies the net shortwave radiation and hence warming simulated over North America. In the summertime, CRCM5 produces a mixed response to forestation, with warming over northern needleleaf forests and cooling over southern broadleaf forests. The partitioning of the turbulent heat fluxes plays a major role in determining this response, but it is not robust across models over North America. Implications for the inter-continental transferability of the original LUCAS results are discussed.